KEKERASAN VERBAL DALAM KOMENTAR DI INSTAGRAM - Prasetya, Surya Eko; Faizah, Hasnah; Sinaga, Mangatur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to describe the forms of verbal violence. This research method is qualitative-descriptive. The data source comes from writings commenting on the posts of accounts on instagram that were uploaded from January to May 2019 with a total of 50 data findings. Data collected using documentation techniques in the form of screenshoot and analyzed by linking to the theory used. Based on the results of the study, four forms of verbal violence were found, namely (1) verbal violence that points to specific body parts with 15 finding data; (2) verbal violence that points to certain animals as much as 25 data; (3) verbal violence that refers to certain creatures as much as 28 data, and; (4) verbal violence in the form of harsh word as much as 32 data.Â Key Words: Verbal Violence and Instagram